(untitled) - Forman, Harrison (New York, 1950)
Content: prologue, crisis, nanking, the doldrums, yangtze crossing, Shanghai on the eve, battle of Shanghai, liberation, changeover, readjustment, settling in,...
Keywords: Communism,Chủ nghĩa cộng sản; China,Trung Quốc